Morphological and thermal characterization of zirconia/hydroxyapatite composites prepared via sol-gel for biomedical applications. Issue 2 (1st February 2019) - Catauro, M.; Bollino, F.; Tranquillo, E.; Tuffi, R.; Dell'Era, A.; Ciprioti, S. Vecchio
Abstract: The thermal behavior of pure ZrO2 and hydroxyapatite (denoted as Z and HAp, respectively), as well as three composites with different content of Z and HAp (Z90HAp10, Z70HAp30 and Z50HAp50) prepared via sol-gel method has been studied by thermogravimetry (TG) and first-order derivative of TG up to 1200 °C under inert gas atmosphere. Dehydration, loss of alcohol and acetylacetone and a multi-step thermal decomposition processes has been identified by analyzing the gases evolved in each step by Fourier transform infrared spectroscopy (FTIR). Fresh samples of Z-rich composites undergo an abrupt ejection of material from the crucible around 200 °C with noticeable increase of the sample temperature. During the occurrence of this phenomenon FTIR spectra demonstrated the evolution of gases (CO, CO2, acetone and ethylene) due to the simultaneous decomposition of acetylacetone and ethanol, not present in the samples calcined at 120 °C. As far as the structural study is concerned, pure Z crystallizes at 1000 °C in the monoclinic system, but the presence of HAp in the composite materials enables the crystallization of Z in the tetragonal phase. Finally, the amorphization degree increases with increasing the content of Z in all the composites treated at 600 and 1000 °C.